Identification and Analysis of bZIP Family Genes in Potato and Their Potential Roles in Stress Responses - Wang, Qi; Guo, Cun; Li, Zhiyuan; Sun, Jinhao; Wang, Dong; Xu, Liangtao; Li, Xiaoxu; Guo, Yongfeng (Frontiers in Plant Science, 2021)
The bZIP proteins comprise one of the largest transcription factor families, and play important roles in plant growth and development, senescence, metabolic reactions, and stress responses. In this study, 49 bZIP transcription factor-encoding genes (StbZIPs) on the potato genome were identified and analyzed. The 49 StbZIP genes which are located on 12 chromosomes of the potato genome, were divided into 11 subgroups together with their Arabidopsis homologs based on the results of phylogenetic analysis. Gene structure and protein motif analysis revealed that members from the same subgroup often possessed similar exon/intron structures and motif organizations, further supporting the results of the phylogenetic analysis. Syntenic analysis indicated the existence of gene duplication events which might play an important role in the expansion of the bZIP gene family in potato. Expression of the StbZIP genes was analyzed in a variety of tissues via RNA-Seq data, suggesting functional diversity. Several StbZIP genes were found to be induced by different stress conditions. For example, expression of StbZIP25, the close homolog of AtbZIP36/ABF2, was significantly up-regulated by salt and drought stress treatments. The StbZIP25-GFP fusion protein was found to be located in the nucleus. Overexpression of StbZIP25 enhanced salt tolerance in Arabidopsis. The results from this study imply potential roles of the bZIP family genes in stress response of potato.